Green recovery : get lean, get smart, and emerge from the downturn on top - Winston, Andrew S. (Harvard Business Press, 2009)
In Green Recovery, sustainability expert Andrew Winston argues that environmental challenges and increasing "green" awareness have not dissipated in the wake of the financial crisis. Business leaders must face both problems simultaneously. Fortunately, some of the same strategies that address environmental issues can help companies survive today's economic conditions--and prosper when the good times return. Winston explains that going green is essentially about doing more with less. Viewed through this lens, green initiatives transform from costly luxuries to powerful recession-fighting, profit-making tools. The book shows how leading companies--including Boeing, Disney, DuPont, Microsoft, Procter & Gamble, Toyota, and Wal-Mart--are ramping up efficiency, innovation, and employee motivation to save money quickly and preserve capital that can be reinvested for future growth. And this book provides a road map for using green initiatives to: get lean; get smart; get creative; and get engaged, so you can survive today's turmoil--and chart a winning path to the future.--From publisher description.